Fashaf Electrical Engineering (wiring services) / Mohd Shahidan Omar ... [et al.] - Omar, Mohd Shahidan; Gadli, Mohd Fadzil; Bakhri, Mohd Faizal; Abdullah, Ajizi; Mohd Rejab, Nurhijriah; Meor Hamzah, Nur Hamiza (Faculty of Electrical Engineering, 2002)
FASHAF Electrical Engineering is a business that focuses in wiring and electrical equipment installation service.